Dronedarone, amiodarone and other antiarrhythmic drugs, and acute liver injuries: a case-referent study. (1st September 2018) - Grimaldi-Bensouda, Lamiae; Wedemeyer, Heiner; Wiegand, Johannes; Lohse, Ansgar W.; Benichou, Jacques; Rossignol, Michel; Larrey, Dominique; Abenhaim, Lucien; Poynard, Thierry; Schott, Eckart; ,
Abstract: Background: Spontaneous reports of acute liver injuries (ALI) in patients taking dronedarone triggered an EMA alert in 2011. This study aimed to assess the risk of ALI for class III antiarrhythmic drugs controlling for the use of other potential ALI-inducing drugs. Methods: Between 2010 and 2014, consecutive ALI cases (≥50 years-old) were identified across Germany. ALI was defined as a new increase in at least one of the transaminases ≥3 times the upper limit of normal (ULN) or ≥2 ULN if alkaline phosphatase, with ("definite" case) or without ("biochemical" case) suggestive signs/symptoms of ALI, excluding other liver diseases. Recruited community controls were matched to cases on gender, age and inclusion date. Exposure to antiarrhythmic drugs and co-medication up to 2 years before ALI onset was informed by patients and confirmed by physicians' prescriptions. Adjusted Odds Ratios (aOR) were obtained from conditional multivariable logistic regressions, adjusted for a multivariate disease risk score and co-medication. Results: 252 cases and 1081 matched controls were included (59.1% females; mean age: 64 years). Exposure to class III antiarrhythmic drugs was 4.0% in cases and 1.5% in controls, aOR = 3.6 (95% CI: 1.6–8.4). Associations with exposure to dronedarone and amiodarone were respectively 3.1 (95% CI: 0.7–14. 8) and 5.90 (1.7–20.0). Restricting the analysis to definite or severe ALI cases did not change these results. Conclusions: Class III antiarrhythmic drugs were associated with ALI, amiodarone displaying the highest risk, and results were robust to case definitions. Continued vigilance is needed for patients taking these drugs. Highlights: Class I and III antiarrhythmics were associated with elevated odds ratios for ALI. Class II and IV (non-specific) antiarrhythmics were not associated with risk of ALI. Amiodarone displayed the highest OR of 5.90 (95% CI: 1.7–20.0). Dronedarone displayed an OR of 3.1 (95% CI: 0.7–14. 8). Fatal ALI, rare drug-induced events requiring pharmacovigilance, was not addressed.